The Effectiveness of Teamwork in Kasti Ball Sports Among Grade IV Students - Sunggu, Ruth Cahaya Op.; Purba, Jon Roi Tua; Barus, Maria (Jurnal Ilmu Sosial dan Humaniora, 2025)
The objective of this investigation is to ascertain the efficacy of incorporating the game of rounders in the enhancement of the cooperation abilities of elementary school students. The research method employed was a One-Group Pretest–Posttest Design, with 22 students selected through purposive sampling. Instruments utilised included observation diaries for students' collaborative behaviour during the learning process and a collaboration questionnaire. Reliability testing, normality testing, Paired Sample T-Tests, and normalised Gain (N-Gain) calculations were implemented to conduct data analysis. The results indicated a substantial improvement in the cooperation abilities of students following the implementation of an intervention that involved learning through rounders. The Paired Sample T-Test produced a significance value of 0.000 (p < 0.05), which suggests a substantial disparity between the pretest and posttest scores. An average increase of 56.29% was observed in the N-Gain analysis, which is regarded as moderate. Additionally, the pre- and post-intervention phases exhibited a substantial difference (p = 0.042), which supports the notion that the enhancement in cooperation is evident in both the assessment and the actual behaviour on the field. Consequently, the implementation of baseball can be regarded as effective in enhancing the cooperation abilities of students. These results suggest that baseball should be employed as a physical education learning strategy that prioritises the development of students' social values and character, in addition to their motor skills, in accordance with the requirements of a contemporary curriculum